Overexpression of the Maize Sulfite Oxidase Increases Sulfate and GSH Levels and Enhances Drought Tolerance in Transgenic Tobacco - Xia, Zongliang; Xu, Ziwei; Wei, Yangyang; Wang, Meiping (Frontiers in Plant Science, 2018)
Sulfite oxidase (SO) plays a pivotal role in sulfite metabolism. In our previous study, sulfite-oxidizing function of the SO from Zea mays (ZmSO) was characterized. To date, the knowledge of ZmSO’s involvement in abiotic stress response is scarce. In this study, we aimed to investigate the role of ZmSO in drought stress. The transcript levels of ZmSO were relatively high in leaves and immature embryos of maize plants, and were up-regulated markedly by PEG-induced water stress. Overexpression of ZmSO improved drought tolerance in tobacco. ZmSO-overexpressing transgenic plants showed higher sulfate and glutathione (GSH) levels but lower hydrogen peroxide (H2O2) and malondialdehyde (MDA) contents under drought stress, indicating that ZmSO confers drought tolerance by enhancing GSH-dependent antioxidant system that scavenged ROS and reduced membrane injury. In addition, the transgenic plants exhibited more increased stomatal response than the wild-type to water deficit. Interestingly, application of exogenous GSH effectively alleviated growth inhibition in both wild-type and transgenic plants under drought conditions. qPCR analysis revealed that the expression of several sulfur metabolism-related genes was significantly elevated in the ZmSO-overexpressing lines. Taken together, these results imply that ZmSO confers enhanced drought tolerance in transgenic tobacco plants possibly through affecting stomatal regulation, GSH-dependent antioxidant system, and sulfur metabolism-related gene expression. ZmSO could be exploited for developing drought-tolerant maize varieties in molecular breeding.